1995
DOI: 10.1542/peds.96.4.649
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Attitudes Toward Firearm Injury Prevention Counseling in Urban Pediatric Clinics

Abstract: Objectives. To examine characteristics and experiences associated with gun ownership among parents of pediatric patients who attend urban pediatric clinics and to determine the receptivity of these parents to firearm injury prevention counseling. Design. A focus group discussion was followed by a cross-sectional survey. Setting. Four public pediatric clinics in a large metropolitan area were included. Participants. A focus group discussion was held with parents and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(8 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…First, respondents understood and valued the prevention potential of the firearm access question. This finding aligns with our cross-sectional research demonstrating most patients receiving mental health care will answer this question, and prior research indicating that people are generally receptive to firearm injury/suicide prevention practices . Second, respondents described a nuanced understanding of challenges that may drive under-reporting access.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…First, respondents understood and valued the prevention potential of the firearm access question. This finding aligns with our cross-sectional research demonstrating most patients receiving mental health care will answer this question, and prior research indicating that people are generally receptive to firearm injury/suicide prevention practices . Second, respondents described a nuanced understanding of challenges that may drive under-reporting access.…”
Section: Discussionsupporting
confidence: 83%
“…These findings, in combination with prior qualitative stakeholder-informed research, provide a road map for addressing barriers clinical teams may experience with firearm access assessment. This study underscored the need to communicate that the intended purpose of routine questions about firearm access is to support conversations about suicide prevention, not to limit patient autonomy .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Previous research indicates that race may differentiate firearm owners from one another. Some studies have found that race does not impact firearm ownership (e.g., Haught et al, 1995), while others found that those who identified as White were more likely to own firearms (e.g., Farah et al, 1999). Even though the research on race and ownership is inconclusive, there is evidence that subgroups of firearm owners may differ by race.…”
Section: Introductionmentioning
confidence: 99%
“…According to guidelines for qualitative syntheses (25,26), we included only peer-reviewed studies. We excluded two studies that briefly summarized preliminary qualitative data collected for another study (27,28). Papers that were from the same parent study were marked as such (Table 1).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%